Genome-Wide SNP Markers Based on SLAF-Seq Uncover Genetic Diversity of Saccharina Cultivars in Shandong, China - Wang, Xiangyu; Wang, Wenjun; Zhan, Dongmei; Ge, Shanshan; Tang, Liuqing (Frontiers in Marine Science, 2022)
China has an abundance of Saccharina cultivars. Most of them are in Shandong Province. These cultivars have been used for many years, and their genetic structure is likely to change. In this study, 13 Saccharina cultivars that are widely applicated in China were collected from Rongcheng and Changdao and sequenced using SLAF-seq technology. A total of 277.27M reads were obtained with a 12.98× sequencing depth, a mean 87.84% Q30 ratio, and a mean 48.49% GC content. A subset of >300,000 SNPs associated with minor allele frequency (MAF) > 0.05 and integrity > 0.5 was obtained. A phylogenetic tree and a population structure analysis based on the high-confidence SNP data showed that the 13 Saccharina cultivars could be divided into 2 groups. The average nucleic acid diversity (Pi), heterozygosity (Ho), and expected heterozygosity (He) of SNP markers in the populations were 4.38×10-5, 0.249, and 0.265, respectively. The average inbreeding coefficient is 0.198, which is high. The results could provide scientific basis for heterosis in Saccharina breeding and germplasm utilization.